Ability of students to recognize opportunities following implementation of entrepreneurship learning - Kompiang Martina Dinata Putri; I Putu Arya Mulyawan; I Dewa Ayu Agung Tantri Pramawati (Institute of Computer Science (IOCS), 2023)
Entrepreneurship in the world of education aims to form a whole human being (holistic), as a human being who has the character, understanding, and skills as an entrepreneur. This study used observation, interview, documentation techniques, and a purposive sampling technique with the research object being students who were pursuing entrepreneurship education at INSTKI. The purpose of this research is to find out whether after studying entrepreneurship students can see business opportunities around them and foster an interest in entrepreneurship for students. The results of this study state that after studying entrepreneurship in theory and practice, students are able to see business opportunities around them and foster student interest in entrepreneurship